PUBLIC FINANCE IN BOSNIA AND HERZEGOVINA - DOMESTIC LEGAL FRAMEWORK AND EUROPEAN STANDARDS - Vranjes, Nevenko D; Vasiljević Pojašević, Bojana (Politeia, 2019)
Bosnia and Herzegovina is a state of a complex legal and political structure with four levels of administrative authority - the joint institution of Bosnia and Herzegovina, the Republic of  Srpska, the Federation of Bosnia and Herzegovina, and the Brčko District of Bosnia and Herzegovina.  In addition, each level of authority collects and disposes of direct taxes, while indirect taxes are collected through a single system, and their distribution is carried out at the aforementioned levels. There is no single framework for managing public finances, both in organisational and material terms. Bosnia and Herzegovina is in constant credit arrangements with the International Monetary Fund (IMF), which are conditioned by constant reform requirements. Public administration financing is burdened by the hyperinflation of  administrative bodies, by a large number of employees in the public sector, by the lack of  central register of personnel, by complicated public procurement procedures, by the lack of  strategic framework for public finance management, by significant deficiencies observed by audit services, by non-compliance with audit recommendations, by non- transparency of budget spending, by the inefficiency of internal audit,  and by the lack of harmonisation between the domestic legal framework with that of the EU. This paper analyses the existing legal framework of public finances from the aspect of governance, the European Commission's Progress Report on Public Finance in Bosnia and Herzegovina, the SIGMA-OECD Reports on the European Principles of Financial Management in Public Institutions, and the EU Guidelines on Public Finance, and is rounded off by identifying the challenges of harmonisation of the domestic legal framework with that of the EU in the field of public finances, offering operational solutions and recommendations.